Review: Myopia control strategies recommendations from the 2018 WHO/IAPB/BHVI Meeting on Myopia. Issue 11 (26th February 2020) - Ang, Marcus; Flanagan, Judith L; Wong, Chee Wai; Müller, Andreas; Davis, Amanda; Keys, Drew; Resnikoff, Serge; Jong, Monica; Wong, Tien Yin; Sankaridurg, Padmaja
Abstract : Myopia is a major public health problem, particularly in East Asia. In this summary report, we present key findings and recommendations on strategies for myopia control discussed during the meeting jointly organised by the WHO Regional Office for the Western Pacific, the International Agency for the Prevention of Blindness and the Brien Holden Vision Institute. First, myopia prevalence was reported to be increasing, with up to 80% of junior school students with myopia in East Asia. However, common challenges in implementing myopia control strategies on a national level included lack of school screening programme, and paucity of accurate prevalence data. Second, there continues to be broad public misconception about myopia and myopia control, including lack of parental awareness and resistance to wearing spectacles. Third, best practices for myopia management were shared, and recommendations for policy implementation are presented in this review. Key recommendations from this meeting include increased public education to raise parent and teacher awareness; encouragement of increased outdoor time of 2–3 hours per day for schoolchildren—as a practical public health intervention that has been shown to potentially reduce onset and progression of myopia. Governments and non-governmental organisations are encouraged to collaborate, especially education and health ministries to develop national myopia prevention programme. Lastly, it is important to emphasise that the key recommendations, such as increasing outdoor time for schoolchildren, are specific for East Asian nations in the Western Pacific region and may not be entirely applicable for Western nations.